Peningkatan Kualitas Layanan Ambulans Muhammadiyah Yogyakarta - Mafaza Rahadiani, Nadzira; Fadillah, Dinda; Apriliana Fauzia, Musyarofah; Khuluq, Lathiful (Universitas Muhammadiyah Sukabumi, 2023)
This article is a report on the activities of the Independent Learning Independent Campus (MBKM) Humanitarian Project for Social Welfare Science students. Considering the urgency to create standard standards in providing services to the community, Muhammadiyah Ambulance together with MBKM students realized the formation of Standard Operating Procedures (SOP). This SOP will be a standard and structured guide for Muhammadiyah Ambulance drivers, crew, and volunteers in carrying out their duties. Creating, finalizing, and implementing good SOPs is an important step to improve the quality and effectiveness of Muhammadiyah Ambulance services, as well as minimizing the risks associated with the absence of SOPs or inconsistent implementation. Service operational standards as a requirement in service mobility will contain five important things, including first, service management standards, second, driver and crew rules, third, ethics in driving, fourth regarding unit and service procedures, and fifth, additional rules required in service. This SOP was created through several stages, namely operational update assessment, planning, focus group discussion (FGD), review, validation and legitimacy, policy implementation, and evaluation. All stages have been carried out thoroughly and maximally over a period of three months, resulting in a structured standard guide in the form of Standard Operational Procedures for Muhammadiyah Ambulance Services. This SOP has now been used in your Ambulance service. The planning for making this SOP was carried out well thanks to the collaboration between MBKM humanitarian project students and the Yogyakarta Special Region Ambulance Service agency.